Analysis of factors affecting families ability in early detection of high risk pregnancies - Nursalam (Wolters Kluwer Medknow Publications, 2020)
The purpose of this study is to analyze the factors that influence the ability of families to detect early high risk of pregnancy. The study design used observational analytic cross-sectional study approaches. The sample size consisted of 120 families of pregnant women working in the Primary Health Care working area in the city of Surabaya, East Java, Indonesia. The independent variables are personal factors, resources, the influence of cognition, interpersonal influence, basic values, and commitment. The dependent variable is family ability. Data were collected using a questionnaire that was tested for validity and reliability. Logistic regression is used to analyze the results. Complementary education (p = 0.001), level of knowledge (0.002), self-esteem (p = 0.047), self-motivation (p = 0.022), and previous behavior (p = 0.010) affect personal factors. Family connection (p = 0,001), community resources (p = 0,003), and competing role demand (0,008) influence the resources factor. Benefits (p = 0,000), obstacles (p = 0.026), and self-efficacy (p = 0,000) affect the influence of cognition. Family support (p = 0,000) and midwife support (p = 0.024) influence interpersonal factors. Responsibility (p = 0.047), attention (p = 0,000) and care (p = 0.046) affect the basic values. Affective (p = 0.011), Continuance (p = 0.001), and Normative (p = 0.012) affect the commitment factor. Introduction (p = 0.000), decision (p = 0.008), care (p = 0.001) and utilization (p = 0.001). The connection of family connection and interpersonal factors, including family support and midwife support, is very important to improve the ability of families in early detection of high risk pregnancies.